2020
DOI: 10.15446/acag.v69n1.79834
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high planting densities and arrangements on yield and fruit development of Musa AAA Simmonds

Abstract: Banana is one of the most abundantly consumed fruits in the world for its contribution to human nutrition, including an important content of potassium.  Given the social contribution of this crop in the cropping areas of Colombia, it is necessary to develop agronomic management strategies that contribute to increasing productivity and offering alternatives that regulate the effects of climate seasonality on banana production in the Urabá region of Colombia.  For this purpose, different planting densities (2,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…2). These variables are important from the agronomic point of view for cultivation systems with high densities and irrigation systems; these data can be used as a reference point and are consistent with those indicated by Barrera et al (2020) where the triangle distribution contributed to a greater bunch mass gain without affecting the exportable quality. The proposed values are similar to those of Santos et al (2015) for the cultivation of bananas.…”
Section: Gas Exchangesupporting
confidence: 75%
See 1 more Smart Citation
“…2). These variables are important from the agronomic point of view for cultivation systems with high densities and irrigation systems; these data can be used as a reference point and are consistent with those indicated by Barrera et al (2020) where the triangle distribution contributed to a greater bunch mass gain without affecting the exportable quality. The proposed values are similar to those of Santos et al (2015) for the cultivation of bananas.…”
Section: Gas Exchangesupporting
confidence: 75%
“…Lanuakum et al (2015) suggested that a negative relationship between canopy temperature and other performance attributes, such as temperature and plant density, influence banana productivity. Further, other related studies have indicated that planting densities and plant distribution influence the productivity of the banana crop (Rodriguez et al 2007;Barrera et al, 2020).…”
Section: Correlation Between the Variables Of Gas Exchange And Productionmentioning
confidence: 97%
“…Our analyses would suggest that in the environmental conditions of the Urabá, the cultivation system in HD at a second cycle is feasible, because the effect of the treatments, despite presenting statistical differences in the height of the return sucker, this is adequate, as long as the price opportunities in the market are competitive, or the fruit is used to win quotas for exporting boxes, since the same number of boxes delivered in the first semester (good price), is received in the second semester, with the same commercial value and number of boxes, because as plantation density increases, it contributes to increasing productivity per hectare (Barrera et al 2020). These results are harmony with those obtained by Chaudhuri & Baruah (2010) who found that planting density significantly affected both the number of suckers and their production.…”
Section: Resultsmentioning
confidence: 99%